2016
DOI: 10.1002/jcb.25816
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Inhibits Proliferation, Invasion, and Epithelial–Mesenchymal Transition by Increasing miR‐200c Expression in HCT‐116 Colorectal Cancer Cells

Abstract: our findings revealed a major role of resveratrol in apoptosis, invasion, and switching of EMT to MET phenotype through upregulation of miR-200c in CRC. J. Cell. Biochem. 118: 1547-1555, 2017. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 46 publications
1
46
0
Order By: Relevance
“…miR‐200c plays an important role in several biological processes such as EMT, apoptosis, cell invasion, metastasis, and drug resistance (Humphries & Yang, ). Our previous result showed that miR‐200c suppressed the EMT process and increased chemosensitivity of HCT‐116 cells (Heydari et al, ; Karimi Dermani et al, ).…”
Section: Discussionmentioning
confidence: 95%
“…miR‐200c plays an important role in several biological processes such as EMT, apoptosis, cell invasion, metastasis, and drug resistance (Humphries & Yang, ). Our previous result showed that miR‐200c suppressed the EMT process and increased chemosensitivity of HCT‐116 cells (Heydari et al, ; Karimi Dermani et al, ).…”
Section: Discussionmentioning
confidence: 95%
“…Recently investigation on the anti‐cancer properties of substances has been widely considered. Therefore, studying the mechanism of interaction of substances with DNA is very important . In this section, to gain a better understanding of the interaction between new polysubstituted pyrroles and DNA, we used UV–Visible spectroscopy, circular dichroism spectroscopy and viscosity measurements.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidence shows that natural agents, such as dietary polyphenols (curcumin, resveratrol, and tea polyphenols), have chemopreventive effects and may be combined with conventional therapy for more effective treatment of cancer [21][22][23]. Green tea polyphenols, such as EGCG, exhibit potential activity against various tumor cells through the regulation of multiple signaling pathways.…”
Section: Discussionmentioning
confidence: 99%